Biomarker Tools to Design Clinical Vaccines Determined from a Study of Annual Listeriosis Incidence in Northern Spain - Calderon-Gonzalez, Ricardo; Teran-Navarro, Hector; Marimon, José María; González-Rico, Claudia; Calvo-Montes, Jorge; Frande-Cabanes, Elisabet; Alkorta-Gurrutxaga, Miriam; Fariñas, M. C.; Martínez-Martínez, Luis; Perez-Trallero, Emilio; Alvarez-Dominguez, Carmen (Frontiers in Immunology, 2016)
Two regions of northern Spain, Gipuzkoa and Cantabria present high annual incidence of listeriosis (1.86 and 1.71 cases per 100,000 inhabitants, respectively). We report that the high annual incidences are a consequence of infection with highly virulent L. monocytogenes isolates linked to fatal outcomes in elderly patients with cancer. In addition, listeriosis patients with cancer present low IL-17A/IL-6 ratios and significantly reduced levels of anti-GAPDH1-22 antibodies, identified as two novel biomarkers of poor prognosis. Analysis of these biomarkers may aid in reducing the incidence of listeriosis. Moreover, GAPDH1-22 activated monocyte derived dendritic cells of listeriosis patients with cancer seem useful tools to prepare clinical vaccines as they produce mainly Th1 cytokines.